2015
DOI: 10.1177/0363546514563911
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Distal Clavicle Resection in Symptomatic Acromioclavicular Joint Arthritis Combined With Rotator Cuff Tear

Abstract: There was no difference in the clinical evaluations between the combined arthroscopic DCR and RCR group and the isolated RCR group at a minimum 24-month follow-up. Arthroscopic DCR should be carefully considered in patients who have symptomatic ACJ arthritis with RC tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 41 publications
0
47
1
Order By: Relevance
“…While concomitant procedures currently have an unclear effect on the outcome of rotator cuff repairs, 1 , 5 , 17 , 22 , 29 , 33 these procedures are often performed with rotator cuff repairs to address additional aspects of shoulder pathology. We found that the incidence of subacromial decompression was high for both groups but greater in the arthroscopic rotator cuff repair group than in the open group (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While concomitant procedures currently have an unclear effect on the outcome of rotator cuff repairs, 1 , 5 , 17 , 22 , 29 , 33 these procedures are often performed with rotator cuff repairs to address additional aspects of shoulder pathology. We found that the incidence of subacromial decompression was high for both groups but greater in the arthroscopic rotator cuff repair group than in the open group (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed trends in concomitant procedures associated with rotator cuff repair surgery in Medicare patients, as 1 study suggested that the rates of these procedures have been increasing 31 despite there currently being a lack of evidence supporting their use. 1 , 17 , 22 , 29 , 33 …”
mentioning
confidence: 99%
“…Therefore, we judged that the amount of distal clavicle resection should be up to approximately 15 mm to avoid damage to the trapezoid ligament. Several authors have suggested that the critical resection length of the distal clavicle ranges from 5 to 15 mm, but there is still no consensus on the amount required to maintain AC joint stability and prevent contact between the distal clavicle and the acromion [15]. Gartsman et al [1] reported that 1.5 cm was an appropriate resection amount.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this attachment morphology, we believe that an excision of less than 15 mm will not affect AC joint stability. The critical amount of resection remains controversial, with most authors recommending 5-15 mm of resection; however, there is a large variation in reported resection volumes [1,6,10,[12][13][14][15][16]. Arthroscopic resection of the distal clavicle has recently been developed as a less invasive alternative to open surgery that enables preservation of the clavicular attachments of the deltoid and trapezius muscles and faster return to normal activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation